Suboptimal bacteriological quality of household water in municipal Ibadan, Nigeria - Alabi, Olumuyiwa Samuel; Akintayo, Ifeoluwa; Odeyemi, Jesutofunmi S.; Oloche, Jeremiah J.; Babalola, Chibuzor M.; Nwimo, Chukwuemeka; Popoola, Oluwafemi; Mogeni, Ondari D.; Marks, Florian; Okeke, Iruka N. (The American journal of tropical medicine and hygiene, 2024)
Access to potable water is difficult for many African residents. This study evaluated the bacteriological quality of household water collected in the dry and wet seasons across five municipal local government areas (LGAs) in Ibadan, a large city in southwest Nigeria. A total of 447 water samples (dry season, n = 250; wet season, n = 197) were aseptically collected from a random sample of mapped households within Ibadan’s five municipal LGAs. The pH values and total aerobic and coliform bacterial counts were measured, and samples were screened for Escherichia coli, Salmonella, Shigella, and Yersinia by standard phenotypic techniques and multiplex polymerase chain reaction. The most common source of water was well (53.2%), followed by borehole (34%). None of the households used municipal tap water. Cumulatively, aerobic (P = 0.0002) and coliform (P = 0.0001) counts as well as pH values (P = 0.0002) changed significantly between seasons, with increasing and decreasing counts depending on the LGA. Nonpotable water samples were found to be very common during the dry (86.8%) and wet (74.1%) seasons. Escherichia coli spp., as indicators of recent fecal contamination, were isolated from 115 (25.7%) of the household water sources. Thirty three Salmonella, four enteroaggregative E. coli, and four enterotoxigenic E. coli isolates but no Shigella or Yersinia isolates were identified. This study revealed the absence of treated tap water and the poor quality of alternative sources with detectable pathogens in municipal Ibadan. Addressing the city-wide lack of access to potable water is an essential priority for preventing a high prevalence of feco-orally transmitted infections.
Gesehen am 25.11.2024